Crushing responses and optimization of novel sandwich columns. (1st May 2021) - Chen, Huichao; Zhang, Yong; Lin, Jiming; Zhang, Feng; Wang, Yaxuan; Yan, Xiaolei
Highlights: Three corrugated sandwich columns are proposed to improve the energy absorption of the thin-walled structure. Parameters A and N of the core tube have a significant effect on the mechanical properties of the sandwich column. The theoretical model of three corrugated sandwich columns are developed to predict the mean crushing force. The discrete optimization design is performed to obtain the optimal design parameters of the three sandwich columns. Abstract: The paper proposes a design method of the sandwich column with the corrugated sinusoidal core and develops the triangular corrugated sandwich column (TCSC), quadrangular corrugated sandwich column (QCSC) and hexagonal corrugated sandwich column (HCSC). The experimental tests of the TCSC and QCSC with A = 8 and N = 1 are conducted to estimate the crushing responses and the reliability of the numerical model of the sandwich column. The crushing responses are numerically investigated of the TCSC, QCSC and HCSC with different geometrical characteristics and the same mass under the axial impacting load. The results show that the energy absorption of the sandwich column is significantly affected by the geometric parameters A and N of the sinusoidal core tube, and the sandwich design has the large advantage of the energy absorption over corresponding members. Furthermore, the theoretical model of the mean crushing force is derived using the simplified super folding element theory, and the comparisons on experimental result and the finite element analysis demonstrate high prediction accuracy of the theoretical model. Lastly, a numerical optimization is proposed by combining orthogonal experimental design and discrete optimization to obtain the optimal crashworthiness of the sandwich column. Optimization results show that the discrete optimization method can be fast convergence and obtain the optimal design parameters. The energy absorption of the optimal sandwich column is about 10% higher than the initial design. Furthermore, the HCSC has the highest specific energy absorption under the same mass and design constraints.